Building Urban Mobility through Smart Cities and Sustainable Policies - Herlan, Herlan; Elyta, Elyta; Al Qadrie, Syarif Redha Fachmi; Asriadi, Asriadi (Puslatbang KDOD Lembaga Administrasi Negara, 2024)
This study examines how smart cities and sustainable policies build urban mobility. Research data from a highly reputable journal indexed by Scopus yielded 321 documents. The search criteria included the title-abs-key